_Navigating Family Estrangement: Helping Adults Understand and Manage the Challenges of Family Estrangement_ (2024) by Karl Melvin. Routledge. ISBN:9781839973212 - Kat O'Mara (Psychotherapy and Counselling Journal of Australia)
As family estrangement becomes increasingly prevalent, therapists are expected to support clients navigating its emotional, relational, and cultural complexities. In _Navigating Family Estrangement: Helping Adults Understand and Manage the Challenges of Family Estrangement_ (Melvin, 2024), psychotherapist Karl Melvin offers a timely, compassionate, and pragmatic clinical resource. This review highlights Melvin’s trauma-informed, non-pathologising approach, which views estrangement not as failure but as a response to relational injury and, in some cases, a pathway towards psychological safety and personal growth. The book introduces Melvin’s estrangement inquiry model, which integrates established conceptual frameworks such as Scharp’s estrangement continuum and Agllias’s typologies. Through clinical vignettes and personal reflections, Melvin offers a structured yet flexible guide for working with clients experiencing various forms of estrangement, whether temporary, functional or permanent. He also challenges prevailing narratives on reconciliation, and prioritises clients’ agency, emotional ambivalence, and cultural context. Melvin’s attention to language, narrative nuance, and sociocultural dynamics strengthen the book’s therapeutic relevance. The review also notes areas for further development, including deeper explorations of trauma, identity-based estrangement, and peer support.